2007
DOI: 10.1038/sj.jes.7500610
|View full text |Cite
|
Sign up to set email alerts
|

Using satellite derived land cover information for a multi-temporal study of self-reported recall of proximity to farmland

Abstract: Exposure misclassification is a major concern in epidemiologic studies. The potential for misclassification becomes even more problematic when participants are asked to recall historical information. Yet, historical information is important in cancer studies, where latency is long and causative exposures may have occurred years or even decades prior to diagnosis. Even though self-reported proximity to farmland is a commonly used exposure measure, the accuracy of recall is seldom, if ever validated. Geographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A significant strength of this study is its use of a unique control group affected by congenital malformations. Previous studies have shown that biased odds ratios can result in self‐report exposure studies utilizing healthy control groups where cases more accurately recall exposures than controls (Avruskin, Meliker, & Jacquez, 2008; Rull et al, 2006). To mitigate such biases, we specifically used a control group (Williams‐Beuren syndrome) that also has congenital anomalies with a disease pathophysiology and etiology that is entirely different than HPE (Kruszka, Porras, et al, 2018; Morris, 2017; Solomon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A significant strength of this study is its use of a unique control group affected by congenital malformations. Previous studies have shown that biased odds ratios can result in self‐report exposure studies utilizing healthy control groups where cases more accurately recall exposures than controls (Avruskin, Meliker, & Jacquez, 2008; Rull et al, 2006). To mitigate such biases, we specifically used a control group (Williams‐Beuren syndrome) that also has congenital anomalies with a disease pathophysiology and etiology that is entirely different than HPE (Kruszka, Porras, et al, 2018; Morris, 2017; Solomon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This study design is important to rule out potential recall bias inherent in retrospective studies for traumatic health outcomes including birth defects. The specific benefit of having a control group with a congenital anomaly can be seen considering the biased odds ratios that can result in selfreport studies on exposures utilizing healthy control groups [57]. For example, Rull and colleagues [17] explored the association between residential proximity to agricultural crops during pregnancy and neural tube defects by comparing self-reports and land use maps of actual proximity.…”
Section: Discussionmentioning
confidence: 99%
“…Seven papers used satellite imagery in exposure science applications (no health end points). These included validation studies of models derived from satellite imagery (Matthijsen et al, 2000; Maxwell et al, 2006; Rull et al, 2006; AvRuskin et al, 2008), constructing a model of atrazine in a drinking water reservoir using land cover data (Atkinson et al, 2001), estimating deterioration of asbestos cement roofing using hyperspectral imagery (Bassani et al, 2007), and using satellite imagery to document flooding in schools as an indicator of building dampness and potential respiratory risk (Guidry and Margolis, 2005). One paper used satellite imagery and GIS to estimate proximity to different crop types in a study of birth weight (Xiang et al, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%